Enhancing Anxiety Management in Post-Tuberculosis Patients through Psychoeducational Intervention in Baki Community Health Center - Agustaria Budinugroho; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: Tuberculosis is an infectious disease caused by mycobacterium tuberculosis by air-borne transmission. TB patients are at risk of psychosocial disorders during treatment and post-treatment. This study aims to analyze the effect of psychoeducation on the level of anxiety experienced relapse in patients after Tuberculosis treatment.Subjects and Method: This study used a quasi-experimental design of a posttest pretest at the Baki Health Center, Sukoharjo Regency, Central Java, Indonesia from June to July 2023. The sample was 30 people in the treatment group, namely post-tuberculosis treatment patients, and 30 people in the control group by paying attention to the inclusion criteria, the sample was selected in total sampling. The dependent variable is anxiety and the independent variable is psychoeducation. Psychoeducation was provided with intervention for 3 sessions with a time of 25-30 minutes and anxiety was measured by the HALS questionnaire. The data was analyzed by the Mann-Whitney test.Results: After the intervention, the psychoeducational group had a decrease in anxiety scores (Mean = 7; SD= 4.68) than the control group (Mean= 4.07; SD= 3.14) with p=0.006.Conclusion: Psychoeducation for post-tuberculosis treatment patients can continue to be carried out to reduce the level of anxiety about tuberculosis recurrence and awareness of the impact of the disease.